2011
DOI: 10.1523/jneurosci.6467-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 Activity Is Modulated by Cell-Associated Sphingosine-1-Phosphate

Abstract: Sphingosine kinases (SphK) 1 and 2 phosphorylate sphingosine to generate sphingosine-1-phosphate (S1P), a pluripotent lipophilic mediator implicated in a variety of cellular events. Here we show that the activity of β-site APP cleaving enzyme-1 (BACE1), the rate limiting enzyme for amyloid-β peptide (Aβ) production, is modulated by S1P in neurons. Treatment by SphK inhibitor, RNAi knockdown of SphK or overexpression of S1P degrading enzymes decreased BACE1 activity to reduce Aβ production. S1P specifically bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 62 publications
10
158
1
1
Order By: Relevance
“…In addition, S1P (12) and amyloid ␤-peptide (37, 39) neurotoxicity involves calpain and procaspase-12 activation by disruption of ER calcium homeostasis but not by membrane-or mitochondria-targeted signals. In addition, it has been shown recently that cell-associated S1P stimulates the activity of BACE1, the rate-limiting enzyme for amyloid ␤-peptide production (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, S1P (12) and amyloid ␤-peptide (37, 39) neurotoxicity involves calpain and procaspase-12 activation by disruption of ER calcium homeostasis but not by membrane-or mitochondria-targeted signals. In addition, it has been shown recently that cell-associated S1P stimulates the activity of BACE1, the rate-limiting enzyme for amyloid ␤-peptide production (40).…”
Section: Discussionmentioning
confidence: 99%
“…Sphk activity assay was performed according to a previous report [52]. The pellet, P1 (the crude nuclear fraction), or supernatant, S1 (cytosolic to gether with the crude mitochondrial fraction), was resuspended in lysis buffer and used for enzymatic reaction.…”
Section: Measurement Of Sphk1 and Sphk2 Activitymentioning
confidence: 99%
“…S1P synthesized by Sphk2 en hances histone H3 acetylation and is involved in regulation of genes encoding the cyclin-dependent kinase inhibitor p21 and c-fos [19]. The latest data reported by Takasugi et al [52] indicated that the S1P pool synthesized by Sphk2 regulates β-amyloid (Aβ) precursor protein (APP) cleaving enzyme 1 (BACE1) activity and the Aβ level. Sphk1 resides predominantly in the cytosol and is translocated to the plasma membrane followed by ERK1/2-mediated phosphorylation [39,45,47].…”
Section: Introductionmentioning
confidence: 99%
“…Attenuating the activity of Sphk1 or overexpression of the S1P-degrading enzyme S1P phosphatase-1 (SGPP1) or S1P lyase (SGPL1) has been shown to reduce BACE1 activity and therefore Aβ production. Conversely, addition of S1P into microsomal fraction significantly increased BACE1 activity, with accompanying increase in Aβ production in both mouse primary cortical neurons and neuroblastoma 2a (N2a) cells (Takasugi et al, 2011).…”
Section: Lipid Changes Related To Amyloid β-Induced Ad Pathologymentioning
confidence: 96%